A transition metal-based heterojunction nanometer array electrode material and a preparation method and application thereof
The three-step method for preparing transition metal-based heterojunction nanoarray electrode materials solves the problems of insufficient catalytic activity and poor stability in sulfide oxidation reactions, achieving a synergistic improvement in catalytic activity and stability, and providing an economical and sustainable electrocatalytic technology.
Patent Information
- Application Number
- CN202610235927.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-27
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-02-27
AI Technical Summary
Existing electrocatalysts for sulfide oxidation reactions suffer from insufficient catalytic activity and poor stability, especially transition metal selenium/telluride, which fail to effectively meet catalytic requirements in sulfide oxidation reactions.
A three-step method was used to prepare transition metal-based heterojunction nanoarray electrode materials. First, the current collector was reacted with a solution of transition metal salt and organic ligand to generate a precursor array material. Then, it was treated with a metal oxophosphate solution and then reacted with a selenium/tellurium source in a gas-solid reaction at high temperature to form a heterojunction structure.
It significantly improves the catalytic activity and long-term stability of sulfide oxidation reactions, solves the problem of easy deactivation of traditional catalysts, and provides an economical and sustainable electrocatalytic technology path.
Smart Images

Figure CN122061183B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials technology. More specifically, it relates to a transition metal-based heterojunction nanoarray electrode material, its preparation method, and its application. Background Technology
[0002] Sulfur-containing wastewater (such as wastewater containing H2S and SO3) 2- Sulfur (including sulfur dioxide, sulfur dioxide, and sulfur trioxide) is a common pollutant in daily life and industrial activities. Due to its high toxicity, corrosiveness, and malodorous properties, it poses a serious threat to the ecological environment and human health. Oxidizing these low-valence sulfur compounds to high-valence sulfur compounds can convert them into valuable chemical raw materials: for example, sulfuric acid, which can be used in fertilizers, pesticides, and metallurgy; and elemental sulfur, which can be used to produce sulfur, sulfuric acid, and vulcanized rubber. However, traditional treatment methods, such as chemical oxidation, catalytic conversion, and precipitation, generally suffer from high costs, huge energy consumption, and a tendency to cause secondary pollution, making it difficult to meet current environmental protection requirements of green, low-carbon, efficient, and economical treatment. Against this backdrop, there is an urgent need to develop sulfur-containing wastewater treatment technologies that are economical, efficient, and sustainable.
[0003] Electrocatalytic oxidation technology, with its advantages of mild reaction conditions, high treatment efficiency, and environmental friendliness, is considered an ideal alternative to traditional processes. Therefore, preparing highly active and stable catalysts is crucial for ensuring the efficient treatment of sulfur-containing wastewater via electrocatalytic sulfide oxidation (SOR). Currently, research on SOR catalysts largely focuses on noble metal and transition metal sulfide systems; however, these materials generally suffer from insufficient catalytic activity and poor long-term stability, limiting their practical application. To overcome this bottleneck, attention has begun to turn to other members of the chalcogenide family. Transition metal selenium / telluride and transition metal sulfides both belong to the chalcogenide family, but they have been rarely reported in the SOR field. This is mainly because the geometry and electronic properties of existing selenium / telluride compounds do not adequately match the catalytic requirements of SOR.
[0004] Therefore, developing highly active and stable transition metal selenium / telluride-based SOR catalysts is of great significance for promoting the development of electrocatalytic oxidation technology in the field of sulfur-containing wastewater treatment. Summary of the Invention
[0005] The present invention addresses the problems of low activity and poor stability of existing electrocatalysts for sulfide oxidation reactions. Its primary objective is to provide a method for preparing a transition metal-based heterojunction nanoarray electrode material.
[0006] A second objective of this invention is to provide a transition metal-based heterojunction nanoarray electrode material prepared by the aforementioned method.
[0007] A third objective of this invention is to provide the application of the aforementioned transition metal-based heterojunction nanoarray electrode material in sulfide oxidation reactions.
[0008] The above-mentioned objective of this invention is achieved through the following technical solution:
[0009] This invention provides a method for preparing a transition metal-based heterojunction nanoarray electrode material, comprising the following steps: S1: The current collector is placed in a mixed solution containing transition metal salts and organic ligands, and after full reaction and post-processing, metal-organic ligand precursor array material is obtained; S2: The metal-organic ligand precursor array material obtained in step S1 is placed in a solution containing metal oxophosphates for treatment, and after full reaction and post-treatment, metal-organic ligand materials modified with metal oxophosphates are obtained. S3: Under a protective gas atmosphere, the metal-organic ligand material modified with metal oxophosphate obtained in step S2 and the heat conversion source are subjected to a high-temperature gas-solid reaction at 200~700 °C to obtain a transition metal-based heterojunction nanoarray electrode material. The heat conversion source includes a selenium source and / or a tellurium source.
[0010] This study innovatively discovered that when preparing nanoarray electrode materials by simultaneously introducing transition metal salts and metal oxoates in a one-step method, rapid homogeneous nucleation and crystallization are easily triggered, resulting in the formation of precipitates that cannot be effectively grown on NF current collectors. When the precipitated products are loaded onto the electrodes and subjected to SOR testing, their catalytic activity is found to be extremely poor. However, the transition metal-based heterojunction nanoarray electrode material prepared by a three-step method (first reacting the current collector with a transition metal salt-organic ligand solution to generate a precursor array material, then treating it with a metal oxoate solution, and finally reacting it with a selenium / tellurium source at high temperature) effectively solves the problems of insufficient catalytic activity and poor stability of metal-based materials modified with metal selenium / telluride and metal oxoates in sulfide oxidation reactions (SOR), achieving a synergistic improvement in both excellent catalytic activity and long-term stability during the SOR process.
[0011] Preferably, in step S1, the metal in the transition metal salt is selected from at least one of Ti, Mn, Fe, Ni, Cu, Zn, Co, Mo, W, La, Ce, and Eu.
[0012] More preferably, in step S1, the metal in the transition metal salt is selected from at least one of Mn, Fe, Ni, Cu, Zn, and Co.
[0013] Preferably, in step S1, the transition metal salt is selected from at least one of nitrates, acetates, chlorides, carbonates, and sulfates.
[0014] More preferably, in step S1, the transition metal salt is selected from at least one of nitrates, acetates, chlorides, and sulfates.
[0015] Preferably, in step S1, the current collector is selected from at least one of carbon cloth, carbon paper, or metal current collector.
[0016] More preferably, in step S1, the metal current collector is selected from at least one of Fe, Co, Ni, Zn, Al, Ti, and stainless steel.
[0017] Optionally, in step S1, the metal current collector is in the form of at least one of metal foam, metal foil, metal plate or metal mesh.
[0018] Preferably, in step S1, the organic ligand is selected from at least one of imidazole compounds, aromatic carboxylic acid compounds, and aliphatic polyol compounds.
[0019] More preferably, the imidazole compound is selected from at least one of 2-methylimidazole, 2-ethylimidazole, 2,4-dimethylimidazole, benzimidazole, and N-benzoylimidazole.
[0020] More preferably, the aromatic carboxylic acid compound is selected from at least one of 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,4'-biphenyldicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-2,4,4'-tricarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, triphenylcarboxylic acid, trimellitic acid, and pyromellitic acid.
[0021] More preferably, the aliphatic polyol compound is selected from at least one of ethylene glycol, 1,4-butanediol, propylene glycol, pentanediol, hexanediol, and glycerol.
[0022] More preferably, in step S1, the organic ligand is selected from at least one of 1,4-naphthalenedicarboxylic acid, 2-aminoterephthalic acid, biphenyl-2,2'-dicarboxylic acid, pyromellitic acid, benzimidazole, and 1,4-butanediol.
[0023] Preferably, in step S1, the solvent of the mixed solution is selected from at least one of water, N,N-dimethylformamide, methanol, ethanol, isopropanol, butanol, benzyl alcohol, cycloethanol, acetone, diethyl ether, acetonitrile, tetrahydrofuran, pyridine, dimethyl sulfoxide, 1,4-dioxane, dichloromethane, chloroform, and tetrachloroethane.
[0024] More preferably, in step S1, the solvent of the mixed solution is selected from at least one of N,N-dimethylformamide, ethanol, isopropanol, tetrahydrofuran, acetonitrile, 1,4-dioxane, and pyridine.
[0025] Preferably, in step S1, the molar ratio of the transition metal salt to the organic ligand is 1:(0.2~20); more preferably, it is 1:(0.4~16).
[0026] Preferably, in step S1, the ratio of the amount of the transition metal salt to the solvent of the mixed solution is 1 mmol: (0.5~1200) mL; more preferably, it is 1 mmol: (1~1000) mL.
[0027] Preferably, in step S1, the time for the full reaction is 18-30 h.
[0028] Optionally, in step S1, the condition for a complete reaction can be a reaction at room temperature for 24 hours.
[0029] Preferably, in step S1, the post-processing includes washing and drying.
[0030] Optionally, the washing process involves washing with ethanol 2 to 4 times, specifically 3 times.
[0031] Optionally, the drying is oven drying, which is drying at 40~80 ℃ for 8~16 h, specifically drying at 60 ℃ for 12 h.
[0032] Preferably, in step S2, the metal in the metal oxometalate is selected from at least one of Sn, V, Mo, W, Ge, and Nb.
[0033] Preferably, in step S2, the concentration of the metal oxophosphate is 0.05~10 mmol / L, more preferably 1~5 mmol / L.
[0034] Preferably, in step S2, the temperature for the full reaction is 15~150 ℃, more preferably 25~125 ℃.
[0035] Preferably, in step S2, the time for the full reaction is 1 to 240 min, more preferably 5 to 180 min.
[0036] Preferably, in step S2, the post-processing includes drying.
[0037] Optionally, the drying is performed at 40~80 ℃ for 8~16 h, specifically at 60 ℃ for 12 h.
[0038] Preferably, in step S3, the mass ratio of the metal-organic ligand material modified with metal oxophosphate to the thermal conversion source is 1:(0.5~30), more preferably 1:(1~20).
[0039] Preferably, in step S3, the protective gas is selected from at least one of nitrogen (N2), argon (Ar), and helium (He).
[0040] Preferably, in step S3, the temperature of the high-temperature gas-solid reaction is 300~600 ℃.
[0041] Preferably, in step S3, the gas flow rate of the high-temperature gas-solid reaction is 1~70 mL / min, more preferably 2~50 mL / min.
[0042] Preferably, in step S3, the heating rate of the high-temperature gas-solid reaction is 1~20 ℃ / min, more preferably 2~10 ℃ / min.
[0043] Preferably, in step S3, the high-temperature gas-solid reaction time is 0.5~10 h, more preferably 1~6 h.
[0044] Preferably, the tellurium source includes tellurium powder.
[0045] Preferably, the selenium source includes selenium powder.
[0046] Preferably, the metal-organic ligand material modified with metal oxophosphate obtained in step S2 is placed in the middle and downstream of the protective gas, and the heat conversion source is placed upstream of the protective gas.
[0047] This application also provides a transition metal-based heterojunction nanoarray electrode material prepared by the aforementioned preparation method.
[0048] This application also provides the application of the aforementioned transition metal-based heterojunction nanoarray electrode material in sulfide oxidation reactions.
[0049] Furthermore, the sulfide oxidation reaction (SOR) is a chemical reaction process in which a compound containing low-valence sulfur loses electrons and is oxidized into a sulfur-containing compound with a valence state higher than the initial valence state under the action of a catalyst.
[0050] Optionally, the compounds containing low-valence sulfur include compounds containing -2-valent sulfur, compounds containing 0-valent sulfur, compounds containing +2-valent sulfur, and compounds containing +4-valent sulfur.
[0051] Further optionally, the divalent sulfur-containing compounds include sodium sulfide (Na2S), potassium sulfide (K2S), hydrogen sulfide (H2S), ammonium sulfide ((NH4)2S), and zinc sulfide (ZnS).
[0052] Alternatively, the compound containing zero-valent sulfur is elemental sulfur.
[0053] Further, alternatively, the compound containing +2 sulfur includes thioacetic acid.
[0054] Further optionally, the compound containing +4 sulfur includes sulfites, sulfites, and bisulfites.
[0055] The present invention has the following beneficial effects: This invention presents a three-step method for preparing transition metal-based heterojunction nanoarray electrode materials: First, a current collector is reacted with a transition metal salt-organic ligand solution to generate a precursor array material. After treatment with a metal oxometalate solution, it is then reacted with a selenium / tellurium source at high temperature via a gas-solid reaction to obtain the final material. The heterojunction structure of this material optimizes electronic properties and geometry through a synergistic effect, resulting in significantly superior sulfide oxidation reaction (SOR) activity compared to single-phase materials. Simultaneously, it enhances the material's corrosion resistance and structural stability, and its performance can be restored after electrolyte replacement, effectively solving the problem of easy deactivation in traditional catalysts. The preparation process is mild, cost-effective, and environmentally friendly, providing an economical and sustainable electrocatalytic technology pathway for the treatment of sulfur-containing wastewater. Attached Figure Description
[0056] Figure 1 The image shows a SEM image of the NF / Zn2SnO4-ZnTe nanoarray electrode material prepared in Example 1.
[0057] Figure 2 This is a SEM image of the CC / CuGeO3-CuTe2 nanoarray electrode material prepared in Example 2.
[0058] Figure 3 This is a SEM image of the IF / MnV2O6-MnTe2 nanoarray electrode material prepared in Example 3.
[0059] Figure 4 This is a SEM image of the SS / NiNb2O6-NiSe2 nanoarray electrode material prepared in Example 4.
[0060] Figure 5 This is a SEM image of the CF / CoMoO4-CoSe2 nanoarray electrode material prepared in Example 5.
[0061] Figure 6 The image shows a SEM image of the TM / FeWO4-FeSe2 nanoarray electrode material prepared in Example 6.
[0062] Figure 7 The image shows a SEM image of the NF / Zn2SnO4-Zn-H2NDC nanoarray electrode material prepared in Comparative Example 3.
[0063] Figure 8 The LSV diagrams show the electrocatalytic SOR of the nanoarray electrode materials in Example 1 and Comparative Examples 1 and 2.
[0064] Figure 9The stability test results of the nanoarray electrode materials used in Example 1 and Comparative Examples 1 and 2 for electrocatalytic SOR are shown.
[0065] Figure 10 The LSV diagram shows the electrocatalytic SOR of the comparative 3-nanometer material.
[0066] Figure 11 The LSV diagrams show the electrocatalytic SOR of the nano-array electrode materials in Example 2 and Comparative Examples 4 and 5.
[0067] Figure 12 The LSV diagrams are for the electrocatalytic SOR of the nano-array electrode materials in Example 3 and Comparative Examples 6 and 7.
[0068] Figure 13 The LSV diagrams show the electrocatalytic SOR of the nano-array electrode materials in Example 4 and Comparative Examples 8 and 9.
[0069] Figure 14 The LSV diagrams show the electrocatalytic SOR of the nano-array electrode materials in Example 5 and Comparative Examples 10 and 11.
[0070] Figure 15 The LSV diagrams are for the electrocatalytic SOR of the nano-array electrode materials in Example 6 and Comparative Examples 12 and 13. Detailed Implementation
[0071] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.
[0072] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0073] Example 1: NF / Zn2SnO4-ZnTe nanoarray electrode material The preparation method of the NF / Zn2SnO4-ZnTe nanoarray electrode material includes the following steps: (1) Add 0.05 mmol of zinc acetate (Zn(CH3COO)2) 0.8 mmol of 1,4-naphthalenedicarboxylic acid (H2NDC) and 2H2O were dissolved in a well-mixed N,N-dimethylformamide-ethanol solvent (volume ratio of 5:1, total volume 50 mL). After stirring thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixed solution, a 1×3 cm piece of cleaned nickel foam (NF) was placed in it and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain zinc-naphthalenedicarboxylic acid precursor array material (NF / Zn-H2NDC).
[0074] (2) Immerse the NF / Zn-H2NDC obtained in step (1) in 3 mmol / L Na4SnO4 solution with water as solvent. The mixture was stirred in a 3H2O solution at 100 °C for 60 min. After the reaction was completed, the mixture was removed and dried in a forced-air drying oven at 60 °C for 12 h to obtain the NF / Zn2SnO4-H2NDC material.
[0075] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the tellurium powder in the upstream. The mass ratio of the material to the tellurium powder is 1:5. Under a nitrogen atmosphere, the flow rate is controlled at 5 mL / min. The temperature is increased from room temperature to 400℃ at a heating rate of 3℃ / min. Heat treatment is carried out at 400℃ for 2 h. After the program is completed, the material is naturally cooled to obtain the NF / Zn2SnO4-ZnTe nanoarray electrode material.
[0076] The morphology of the obtained materials was characterized using scanning electron microscopy (SEM), such as... Figure 1 As shown, the nanorod-like structures are uniformly distributed on the NF current collector.
[0077] Example 2 CC / CuGeO3-CuTe2 nanoarray electrode material The preparation method of the CC / CuGeO3-CuTe2 nanoarray electrode material includes the following steps: (1) Dissolve 5 mmol copper acetate (Cu(CH3COO)2·H2O) and 2 mmol 2-aminoterephthalic acid (ATA) in 50 mL isopropanol (IPA) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm carbon cloth (CC) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain copper-2-aminoterephthalic acid precursor array material (CC / Cu-ATA).
[0078] (2) The CC / Cu-ATA obtained in step (1) was immersed in a 2.0 mmol / L sodium germanate (Na2GeO3) solution with ethylene glycol (EG)-water (volume ratio of the two is 1:1, total volume is 50 mL) as solvent, stirred at 125 °C for 5 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain CC / CuGeO3-ATA material.
[0079] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the tellurium powder in the upstream. The mass ratio of the material to the tellurium powder is 1:10. Under the atmosphere of argon, the flow rate is controlled at 10 mL / min. The temperature is increased from room temperature to 450℃ at a heating rate of 5℃ / min. Heat treatment is carried out at 450℃ for 4 h. After the program is completed, the material is naturally cooled to obtain CC / CuGeO3-CuTe2 nanoarray electrode material.
[0080] The morphology of the obtained material was characterized using SEM, such as... Figure 2 As shown, the uniformly distributed nanorod-like structures on the CC current collector are visible.
[0081] Example 3: IF / MnV2O6-MnTe2 nanoarray electrode material The preparation method of the IF / MnV2O6-MnTe2 nanoarray electrode material includes the following steps: (1) Dissolve 1 mmol of manganese chloride (MnCl2·4H2O) and 8 mmol of biphenyl-2,2'-dicarboxylic acid (BPDC) in 50 mL of tetrahydrofuran (THF) solvent. Stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture. Place a clean 1×3 cm piece of foamed iron (IF) in it and carry out a solvothermal reaction at room temperature for 24 h. Wash the reacted material three times with ethanol and dry it in a forced-air drying oven at 60 ℃ for 12 h to obtain manganese-biphenyl-2,2'-dicarboxylic acid precursor array material (IF / Mn-BPDC).
[0082] (2) The IF / Mn-BPDC obtained in step (1) was immersed in a 4.0 mmol / L ammonium vanadate (NH4VO3) solution with propylene glycol (PG)-water (volume ratio of the two is 3:1, total volume is 50 mL) as solvent, stirred at 75 °C for 15 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain IF / MnV2O6-BPDC material.
[0083] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the tellurium powder in the upstream. The mass ratio of the material to the tellurium powder is 1:2. Under a nitrogen atmosphere, the flow rate is controlled at 2 mL / min. The temperature is increased from room temperature to 600℃ at a heating rate of 8℃ / min. Heat treatment is carried out at 600℃ for 6 h. After the program is completed, the material is naturally cooled to obtain the IF / MnV2O6-MnTe2 nanoarray electrode material.
[0084] The morphology of the obtained material was characterized using SEM, such as... Figure 3 As shown, the nanorod-like structures are uniformly distributed on the IF current collector.
[0085] Example 4: SS / NiNb2O6-NiSe2 nanoarray electrode material The preparation method of the SS / NiNb2O6-NiSe2 nanoarray electrode material includes the following steps: (1) Dissolve 0.25 mmol nickel sulfate (NiSO4·6H2O) and 0.25 mmol trimesic acid (TMA) in 50 mL acetonitrile (ACN) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm stainless steel (SS) piece in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain nickel-trimethylammonium phosphate precursor array material (SS / Ni-ACN).
[0086] (2) The SS / Ni-ACN obtained in step (1) was immersed in a 5.0 mmol / L lithium niobate (LiNbO3) solution with methanol-glycerol (Gly) (volume ratio of the two is 2:1, total volume is 50 mL) as solvent, stirred at 50 °C for 30 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain SS / NiNb2O6-ACN material.
[0087] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:1. Under the atmosphere of argon, the flow rate is controlled at 15 mL / min. The temperature is increased from room temperature to 350℃ at a heating rate of 2℃ / min. Heat treatment is carried out at 350℃ for 1 h. After the program is completed, the material is naturally cooled to obtain the SS / NiNb2O6-NiSe2 nanoarray electrode material.
[0088] The morphology of the obtained material was characterized using SEM, such as... Figure 4 As shown, the nanosheet-like structure is uniformly distributed on the SS current collector.
[0089] Example 5: CF / CoMoO4-CoSe2 nanoarray electrode material The preparation method of the CF / CoMoO4-CoSe2 nanoarray electrode material includes the following steps: (1) Add 4 mmol of cobalt nitrate (Co(NO3)2) 16 mmol of benzimidazole (BZI) and 6 H2O were dissolved in 50 mL of 1,4-dioxane (DOX) solvent and stirred thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture. A 1×3 cm piece of cleaned cobalt foam (CF) was placed in the mixture and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain the cobalt-benzimidazole precursor array material (CF / Co-BZI).
[0090] (2) Immerse the CF / Co-BZI obtained in step (1) in a 1 mmol / L ammonium molybdate ((NH4)6Mo7O) solution containing ethanol-methyl acetate (MA) (volume ratio of 2:1, total volume 50 mL). 24 The mixture was stirred in a 4H2O solution at 25 °C for 180 min. After the reaction was completed, the mixture was removed and dried in a forced-air drying oven at 60 °C for 12 h to obtain CF / CoMoO4-BZI material.
[0091] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:20. Under a nitrogen atmosphere, the flow rate is controlled at 50 mL / min. The temperature is increased from room temperature to 300℃ at a heating rate of 5℃ / min. Heat treatment is carried out at 300℃ for 6 h. After the program is completed, the material is naturally cooled to obtain the CF / CoMoO4-CoSe2 nanoarray electrode material.
[0092] The morphology of the obtained material was characterized using SEM, such as... Figure 5 As shown, the CF current collector exhibits a cluster structure composed of nanosheets uniformly distributed on it.
[0093] Example 6: TM / FeWO4-FeSe2 Nanoarray Electrode Material The preparation method of the TM / FeWO4-FeSe2 nanoarray electrode material includes the following steps: (1) Dissolve 2.5 mmol ferrous sulfate (FeSO4·7H2O) and 5 mmol 1,4-butanediol (BDO) in 50 mL pyridine (Py) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm titanium mesh (TM) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain iron-1,4-butanediol precursor array material (TM / Fe-BDO).
[0094] (2) The TM / Fe-BDO obtained in step (1) was immersed in a 1 mmol / L tungsten chloride (WCl6) solution with propylene glycol-ethanol (volume ratio of the two is 1:1, total volume is 50 mL) as solvent, stirred at 75 °C for 60 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain TM / FeWO4-BDO material.
[0095] (3) Place the material obtained in step (2) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:2. Under the atmosphere of argon, the flow rate is controlled at 30 mL / min. The temperature is increased from room temperature to 550℃ at a heating rate of 10℃ / min. Heat treatment is carried out at 550℃ for 4 h. After the program is completed, the material is naturally cooled to obtain the TM / FeWO4-FeSe2 nanoarray electrode material.
[0096] The morphology of the obtained material was characterized using SEM, such as... Figure 6 As shown in the figure, the cluster structure of nanosheets uniformly distributed on the TM current collector is visible.
[0097] Comparative Example 1: NF / Zn2SnO4 Nanoarray Electrode Material Similar to Example 1, except that no tellurization reaction is performed, the preparation method of the NF / Zn2SnO4 nanoarray electrode material includes the following steps: (1) Add 0.05 mmol of zinc acetate (Zn(CH3COO)2) 0.8 mmol of 1,4-naphthalenedicarboxylic acid (H2NDC) and 2H2O were dissolved in a well-mixed N,N-dimethylformamide-ethanol solvent (volume ratio of 5:1, total volume 50 mL). After stirring thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixed solution, a 1×3 cm piece of cleaned nickel foam (NF) was placed in it and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain zinc-naphthalenedicarboxylic acid precursor array material (NF / Zn-H2NDC).
[0098] (2) Immerse the NF / Zn-H2NDC obtained in step (1) in 3 mmol / L Na4SnO4 solution with water as solvent. The mixture was stirred in a 3H2O solution at 100 °C for 60 min. After the reaction was completed, the mixture was removed and dried in a forced-air drying oven at 60 °C for 12 h to obtain the NF / Zn2SnO4-H2NDC material.
[0099] (3) Place the material obtained in step (2) in a tube furnace, and under a nitrogen atmosphere, control the flow rate at 5 mL / min and raise the temperature from room temperature to 400 ℃ at a heating rate of 3℃ / min. Heat treat at 400 ℃ for 2 h, and allow to cool naturally after the program is completed to obtain NF / Zn2SnO4 nanoarray electrode material.
[0100] Comparative Example 2: NF / ZnTe Nanoarray Electrode Material Similar to Example 1, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the NF / ZnTe nanoarray electrode material includes the following steps: (1) Add 0.05 mmol of zinc acetate (Zn(CH3COO)2) Zinc-naphthalenedicarboxylic acid (NF / Zn-H2NDC) precursor array material was obtained by dissolving 0.8 mmol of 1,4-naphthalenedicarboxylic acid (N2NDC) and 0.8 mmol of 1,4-naphthalenedicarboxylic acid (H2NDC) in a well-mixed N,N-dimethylformamide-ethanol solvent (volume ratio 5:1, total volume 50 mL), stirring thoroughly for 10 min (stirrer speed 500 rpm), and then placing a clean 1×3 cm piece of nickel foam (NF) in the solution. The reaction was carried out at room temperature for 24 h using a solvothermal method. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 °C for 12 h. (2) Place the NF / Zn-H2NDC obtained in step (1) in the downstream of the tube furnace and place the tellurium powder in the upstream. The mass ratio of the material to the tellurium powder is 1:5. Under a nitrogen atmosphere, the flow rate is controlled at 5 mL / min. The temperature is increased from room temperature to 400 ℃ at a heating rate of 3 ℃ / min. Heat treatment is carried out at 400 ℃ for 2 h. After the program is completed, the material is naturally cooled to obtain the NF / ZnTe nanoarray electrode material.
[0101] Comparative Example 3: NF / Zn2SnO4-Zn-H2NDC Nanomaterials Similar to Example 1, the difference lies in the simultaneous introduction of transition metal salts and metal oxoates in a one-step process. The preparation method of the NF / Zn2SnO4-Zn-H2NDC nanoarray electrode material includes the following steps: (1) Add 0.025 mmol of zinc acetate (Zn(CH3COO)2) 2H2O), 0.025 mmol Na4SnO4 3H2O and 0.8 mmol of 1,4-naphthalenedicarboxylic acid (H2NDC) were dissolved in a well-mixed N,N-dimethylformamide-ethanol solvent (volume ratio of 5:1, total volume 50 mL). After stirring thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixed solution, a 1×3 cm piece of cleaned nickel foam (NF) was placed in it and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain zinc stannate-zinc-naphthalenedicarboxylic acid precursor array material (NF / Zn2SnO4-Zn-H2NDC).
[0102] The morphology of the obtained material was characterized using SEM, such as... Figure 7 As shown in the figure, no product was observed on the surface of the NF current collector, and its three-dimensional porous framework structure was completely exposed. This indicates that the one-step method simultaneously introduces the above materials, leading to rapid homogeneous nucleation and crystallization, resulting in precipitation. The precipitate cannot grow on the NF current collector.
[0103] Comparative Example 4: CC / CuGeO4 Nanoarray Electrode Material Similar to Example 2, except that no tellurization reaction is performed, the preparation method of the CC / CuGeO3 nanoarray electrode material includes the following steps: (1) Dissolve 5 mmol copper acetate (Cu(CH3COO)2·H2O) and 2 mmol 2-aminoterephthalic acid (ATA) in 50 mL isopropanol (IPA) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm carbon cloth (CC) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain copper-2-aminoterephthalic acid precursor array material (CC / Cu-ATA).
[0104] (2) The CC / Cu-ATA obtained in step (1) was immersed in a 2.0 mmol / L sodium germanate (Na2GeO3) solution with ethylene glycol (EG)-water (volume ratio of the two is 1:1, total volume is 50 mL) as solvent, stirred at 125 °C for 5 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain CC / CuGeO3-ATA material.
[0105] (3) Place the material obtained in step (2) in a tube furnace, and under an argon atmosphere, control the flow rate at 10 mL / min and raise the temperature from room temperature to 450 °C at a heating rate of 5 °C / min. Heat treat at 450 °C for 4 h and allow to cool naturally after the process is complete to obtain CC / CuGeO3 nanoarray electrode material.
[0106] Comparative Example 5: CC / CuTe2 Nanoarray Electrode Material Similar to Example 2, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the CC / CuTe2 nanoarray electrode material includes the following steps: (1) Dissolve 5 mmol copper acetate (Cu(CH3COO)2·H2O) and 2 mmol 2-aminoterephthalic acid (ATA) in 50 mL isopropanol (IPA) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm carbon cloth (CC) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain copper-2-aminoterephthalic acid precursor array material (CC / Cu-ATA).
[0107] (2) The CC / Cu-ATA obtained in step (1) is placed in the downstream of the tube furnace, and the tellurium powder is placed in the upstream. The mass ratio of the material to the tellurium powder is 1:10. Under the atmosphere of argon, the flow rate is controlled at 10 mL / min, and the temperature is increased from room temperature to 450 ℃ at a heating rate of 5 ℃ / min. Heat treatment is carried out at 450 ℃ for 4 h. After the program is completed, it is naturally cooled to obtain the CC / CuTe2 nanoarray electrode material.
[0108] Comparative Example 6: IF / MnV2O6 Nanoarray Electrode Material Similar to Example 3, except that no tellurization reaction is performed, the preparation method of the IF / MnV2O6 nanoarray electrode material includes the following steps: (1) Dissolve 1 mmol of manganese chloride (MnCl2·4H2O) and 8 mmol of biphenyl-2,2'-dicarboxylic acid (BPDC) in 50 mL of tetrahydrofuran (THF) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm piece of foamed iron (IF) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain manganese-biphenyl-2,2'-dicarboxylic acid precursor array material (IF / Mn-BPDC).
[0109] (2) The IF / Mn-BPDC obtained in step (1) was immersed in a 4.0 mmol / L ammonium vanadate (NH4VO3) solution with propylene glycol (PG)-water (volume ratio of the two is 3:1, total volume is 50 mL) as solvent, stirred at 75 °C for 15 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain IF / MnV2O6-BPDC material.
[0110] (3) Place the material obtained in step (2) in a tube furnace, and under a nitrogen atmosphere, control the flow rate at 2 mL / min and raise the temperature from room temperature to 600 ℃ at a heating rate of 8℃ / min. Heat treat at 600 ℃ for 6 h, and allow to cool naturally after the program is completed to obtain the IF / MnV2O6 nanoarray electrode material.
[0111] Comparative Example 7: IF / MnTe2 Nanoarray Electrode Material Similar to Example 3, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the IF / MnTe2 nanoarray electrode material includes the following steps: (1) Dissolve 1 mmol of manganese chloride (MnCl2·4H2O) and 8 mmol of biphenyl-2,2'-dicarboxylic acid (BPDC) in 50 mL of tetrahydrofuran (THF) solvent. Stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture. Place a clean 1×3 cm piece of foamed iron (IF) in it and carry out a solvothermal reaction at room temperature for 24 h. Wash the reacted material three times with ethanol and dry it in a forced-air drying oven at 60 ℃ for 12 h to obtain manganese-biphenyl-2,2'-dicarboxylic acid precursor array material (IF / Mn-BPDC).
[0112] (2) Place the IF / Mn-BPDC obtained in step (1) in the downstream of the tube furnace and place the tellurium powder in the upstream. The mass ratio of the material to the tellurium powder is 1:2. Under a nitrogen atmosphere, the flow rate is controlled at 2 mL / min. The temperature is increased from room temperature to 600 ℃ at a heating rate of 8 ℃ / min. Heat treatment is carried out at 600 ℃ for 6 h. After the program is completed, the material is naturally cooled to obtain the IF / MnTe2 nanoarray electrode material.
[0113] Comparative Example 8: SS / NiNb2O6 nanoarray electrode material Similar to Example 4, except that no selenization reaction is performed, the preparation method of the SS / NiNb2O6 nanoarray electrode material includes the following steps: (1) Dissolve 0.25 mmol nickel sulfate (NiSO4·6H2O) and 0.25 mmol trimesic acid (TMA) in 50 mL acetonitrile (ACN) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm stainless steel (SS) piece in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain nickel-trimethylammonium phosphate precursor array material (SS / Ni-ACN).
[0114] (2) The SS / Ni-ACN obtained in step (1) was immersed in a 5.0 mmol / L lithium niobate (LiNbO3) solution with methanol-glycerol (Gly) (volume ratio of the two is 2:1, total volume is 50 mL) as solvent, stirred at 50 °C for 30 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain SS / NiNb2O6-ACN material.
[0115] (3) Place the material obtained in step (2) in a tube furnace, and under an argon atmosphere, control the flow rate at 15 mL / min and raise the temperature from room temperature to 350 °C at a heating rate of 2 °C / min. Heat treat at 350 °C for 1 h, and allow to cool naturally after the program is completed to obtain the SS / NiNb2O6 nanoarray electrode material.
[0116] Comparative Example 9: SS / NiSe2 Nanoarray Electrode Material Similar to Example 4, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the SS / NiSe2 nanoarray electrode material includes the following steps: (1) Dissolve 0.25 mmol nickel sulfate (NiSO4·6H2O) and 0.25 mmol trimesic acid (TMA) in 50 mL acetonitrile (ACN) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm stainless steel (SS) piece in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain nickel-trimethylammonium phosphate precursor array material (SS / Ni-ACN).
[0117] (2) Place the SS / Ni-ACN obtained in step (1) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:1. Under the atmosphere of argon, the flow rate is controlled at 15 mL / min. The temperature is increased from room temperature to 350 ℃ at a heating rate of 2 ℃ / min. Heat treatment is carried out at 350 ℃ for 1 h. After the program is completed, it is naturally cooled to obtain the SS / NiSe2 nanoarray electrode material.
[0118] Comparative Example 10: CF / CoMoO4 Nanoarray Electrode Material Similar to Example 5, except that no selenization reaction is performed, the preparation method of the CF / CoMoO4 nanoarray electrode material includes the following steps: (1) Add 4 mmol of cobalt nitrate (Co(NO3)2) 16 mmol of benzimidazole (BZI) and 6 H2O were dissolved in 50 mL of 1,4-dioxane (DOX) solvent and stirred thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture. A 1×3 cm piece of cleaned cobalt foam (CF) was placed in the mixture and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain the cobalt-benzimidazole precursor array material (CF / Co-BZI).
[0119] (2) Immerse the CF / Co-BZI obtained in step (1) in 1 mmol / L ammonium molybdate ((NH4)6Mo7O) solvent with ethanol-methyl acetate (MA) (volume ratio of 2:1, total volume 50 mL). 24 The mixture was stirred in a 4H2O solution at 25 °C for 180 min. After the reaction was completed, the mixture was removed and dried in a forced-air drying oven at 60 °C for 12 h to obtain CF / CoMoO4-BZI material.
[0120] (3) Place the material obtained in step (2) in a tube furnace, and under a nitrogen atmosphere, control the flow rate at 50 mL / min, raise the temperature from room temperature to 300 ℃ at a heating rate of 5℃ / min, and perform heat treatment at 300 ℃ for 6 h. After the program is completed, cool naturally to obtain the CF / CoMoO4 nanoarray electrode material.
[0121] Comparative Example 11: CF / CoSe2 Nanoarray Electrode Material Similar to Example 5, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the CF / CoSe2 nanoarray electrode material includes the following steps: (1) Add 4 mmol of cobalt nitrate (Co(NO3)2) 16 mmol of benzimidazole (BZI) and 6 H2O were dissolved in 50 mL of 1,4-dioxane (DOX) solvent and stirred thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture. A 1×3 cm piece of cleaned cobalt foam (CF) was placed in the mixture and subjected to a solvothermal reaction at room temperature for 24 h. The reacted material was washed three times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain the cobalt-benzimidazole precursor array material (CF / Co-BZI).
[0122] (2) Place the CF / Co-BZI obtained in step (1) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:20. Under a nitrogen atmosphere, the flow rate is controlled at 50 mL / min. The temperature is increased from room temperature to 300 ℃ at a heating rate of 5 ℃ / min. Heat treatment is carried out at 300 ℃ for 6 h. After the program is completed, the material is naturally cooled to obtain the CF / CoSe2 nanoarray electrode material.
[0123] Comparative Example 12: TM / FeWO4 Nanoarray Electrode Material Same as Example 6, except that no selenization reaction is performed. The preparation method of the TM / FeWO4 nanoarray electrode material includes the following steps: (1) Dissolve 2.5 mmol ferrous sulfate (FeSO4·7H2O) and 5 mmol 1,4-butanediol (BDO) in 50 mL pyridine (Py) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm titanium mesh (TM) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain iron-1,4-butanediol precursor array material (TM / Fe-BDO).
[0124] (2) The TM / Fe-BDO obtained in step (1) was immersed in a 1 mmol / L tungsten chloride (WCl6) solution with propylene glycol-ethanol (volume ratio of the two is 1:1, total volume is 50 mL) as solvent, stirred at 75 °C for 60 min, and after the reaction was completed, it was taken out and dried in a forced-air drying oven at 60 °C for 12 h to obtain TM / FeWO4-BDO material.
[0125] (3) Place the material obtained in step (2) in a tube furnace, and under an argon atmosphere, control the flow rate at 30 mL / min and raise the temperature from room temperature to 550 ℃ at a heating rate of 10 ℃ / min. Heat treat at 550 ℃ for 4 h, and allow to cool naturally after the program is completed to obtain the TM / FeWO4 nanoarray electrode material.
[0126] Comparative Example 13: TM / FeSe2 Nanoarray Electrode Material Similar to Example 6, except that it is not treated in a solution containing metal oxophosphates, the preparation method of the TM / FeSe2 nanoarray electrode material includes the following steps: (1) Dissolve 2.5 mmol ferrous sulfate (FeSO4·7H2O) and 5 mmol 1,4-butanediol (BDO) in 50 mL pyridine (Py) solvent, stir thoroughly for 10 min (stirrer speed 500 rpm) to obtain a mixture, place a clean 1×3 cm titanium mesh (TM) in it, and carry out a solvothermal reaction at room temperature for 24 h. The reacted material is washed 3 times with ethanol and dried in a forced-air drying oven at 60 ℃ for 12 h to obtain iron-1,4-butanediol precursor array material (TM / Fe-BDO).
[0127] (2) Place the TM / Fe-BDO obtained in step (1) in the downstream of the tube furnace and place the selenium powder in the upstream. The mass ratio of the material to the selenium powder is 1:2. Under the atmosphere of argon, the flow rate is controlled at 30 mL / min. The temperature is increased from room temperature to 550 ℃ at a heating rate of 10 ℃ / min. Heat treatment is carried out at 550 ℃ for 4 h. After the program is completed, it is naturally cooled to obtain the TM / FeSe2 nanoarray electrode material.
[0128] Application Example 1: Performance Testing of Electrocatalytic Sulfide Oxidation (SOR) Electrochemical measurements were performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) with a standard three-electrode system. The performance index for evaluating the activity of the electrocatalytic material was a current density reaching 100 mA cm⁻¹. -2 Required voltage (E) 100 The method for evaluating the stability of electrocatalytic materials is the change in voltage over time under constant current (100 mA), i.e., the chronopotential method (CP).
[0129] The array electrodes (cut into 1×1 cm pieces) were prepared according to Examples 1-6 or Comparative Examples 1, 2, 4-13. 2The working electrode was prepared using the material obtained in Comparative Example 3 as follows: The precipitate obtained in Comparative Example 3 (with the same loading amount as the working electrode prepared in Example 1, calculated according to the mass difference before and after loading of the current collector in Example 1) was dispersed in a mixed solution containing 483.8 μL water, 120.95 μL ethanol, and 30.24 μL 5wt% Nafion. The mixture was then sonicated for about 30 min to obtain a homogeneous catalyst dispersion. 3 μL of the catalyst dispersion was then dropped onto the NF electrode. The electrode was dried overnight at room temperature to obtain the working electrode. The electrocatalytic activity and stability of the samples were studied in a three-electrode system using a carbon rod as the counter electrode and an Hg / HgO (immersed in 1.0 M KOH solution) electrode as the reference electrode. Electrocatalytic activity was tested under stirring in a sulfide-containing electrolyte (1 M NaOH + 1 M Na₂S, pH = 13.74). Catalyst activation was achieved by CV (-0.90~0 V vs. Hg / HgO). After the CV results stabilized, the LSV curve (-0.90~0 V vs. Hg / HgO) was measured, and the LSV curve was compensated for with 95% iR. Electrocatalytic stability was tested under stirring in a sulfide-containing electrolyte (1 M NaOH + 1 M Na₂S, pH = 13.74). Catalyst activation was achieved by CV (-0.90~0 V vs. Hg / HgO). After the CV results stabilized, the catalyst was stabilized at a current density of 100 mA cm⁻¹. -2 The stability was tested using the chronopotential method. During the test, to ensure sufficient sulfide content in the electrolyte solution, the solution was replaced every 24 hours. The potential value E(RHE) was converted from E(Hg / HgO) according to the formula E(RHE) = E(Hg / HgO) + 0.0977 + 0.05916 × pH.
[0130] The SOR activity and stability of Example 1 (NF / Zn2SnO4-ZnTe), Comparative Example 1 (NF / Zn2SnO4), and Comparative Example 2 (NF / ZnTe) were tested, and the results are shown in [reference to relevant documentation]. Figure 8 and Figure 9 .
[0131] The SOR activity of Comparative Example 3 (NF / Zn2SnO4-Zn-H2NDC) was tested, and the results are shown in [link to results]. Figure 10 .
[0132] Depend on Figure 8 It is evident that, for the activity of SOR, NF / Zn2SnO4-ZnTe has a smaller E0 compared to NF / Zn2SnO4 and NF / ZnTe. 100 E 100vs. RHE are respectively NF / Zn₂SnO₄-ZnTe (0.271 V) < NF / ZnTe (0.384 V) < NF / Zn₂SnO₄ (0.518 V). From Figure 9 it can be seen that for the stability of SOR, NF / Zn₂SnO₄-ZnTe can operate stably for 96 h at a current density of 100 mA cm -2 , while the performance of NF / ZnTe and NF / Zn₂SnO₄ decreases significantly after 24 h and 10 h of operation, respectively. As time increases, the voltage values of NF / Zn₂SnO₄-ZnTe, NF / ZnTe and NF / Zn₂SnO₄ all increase, but the voltage values of NF / ZnTe and NF / Zn₂SnO₄ increase faster. After replacing the sulfide-containing electrolyte solution, the voltage value of NF / Zn₂SnO₄-ZnTe can return to the previous level, while the voltage values of NF / ZnTe and NF / Zn₂SnO₄ cannot, which demonstrates the excellent stability of NF / Zn₂SnO₄-ZnTe. The above experimental results show that compared with single-phase materials that have not been treated with metal oxysalt solution or tellurized, the transition metal telluride-based heterojunction nanoarray electrode has superior activity and stability in SOR.
[0133] From Figure 10 it can be seen that the response capability of NF / Zn₂SnO₄-Zn-H₂NDC to the sulfide oxidation reaction is relatively limited, the increase of current density with the increase of potential is extremely small, and the polarization curve presents an almost horizontal state, indicating that this material is not suitable as an SOR electrocatalyst, and its catalytic activity cannot meet the requirements of practical applications.
[0134] Application Example 2 Performance Test of Electrocatalytic Sulfide Oxidation Reaction (SOR) SOR activity tests were carried out on Example 2 (CC / CuGeO₃-CuTe₂), Comparative Example 4 (CC / CuGeO₃) and Comparative Example 5 (CC / CuTe₂). The test method is the same as that in Application Example 1, and the results refer to Figure 11 .
[0135] From Figure 11 it can be seen that for the activity of SOR, compared with CC / CuGeO₃ and CC / CuTe₂, CC / CuGeO₃-CuTe₂ has a smaller E 100 , and the E 100 vs. RHE are respectively CC / CuGeO₃-CuTe₂ (0.327 V) < CC / CuTe₂ (0.459 V) < CC / CuGeO₃ (0.488 V). The above experimental results show that compared with single-phase materials that have not been treated with metal oxysalt solution or tellurized, the transition metal telluride-based heterojunction nanoarray electrode has superior activity in SOR.
[0136] Application Example 3 Performance Test of Electrocatalytic Sulfide Oxidation Reaction (SOR) The SOR activity test was carried out on Example 3 (IF / MnV₂O₆-MnTe₂), Comparative Example 6 (IF / MnV₂O₆) and Comparative Example 7 (IF / MnTe₂). The test method was the same as that in Application Example 1, and the results refer to Figure 12 .
[0137] It can be seen from Figure 12 that in terms of SOR activity, IF / MnV₂O₆-MnTe₂ has a smaller E than IF / MnV₂O₆ and IF / MnTe₂ 100 , and the E 100 vs. RHE values are respectively IF / MnV₂O₆-MnTe₂ (0.338 V) < IF / MnTe₂ (0.425 V) < IF / MnV₂O₆ (0.502 V). The above experimental results show that compared with the single-phase materials that have not been treated with metal oxysalt solution or tellurized, the transition metal telluride-based heterojunction nanoarray electrode has more excellent activity in SOR.
[0138] Application Example 4 Performance Test of Electrocatalytic Sulfide Oxidation Reaction (SOR) The SOR activity test was carried out on Example 4 (SS / NiNb₂O₆-NiSe₂), Comparative Example 8 (SS / NiNb₂O₆) and Comparative Example 9 (SS / NiSe₂). The test method was the same as that in Application Example 1, and the results refer to Figure 13 .
[0139] It can be seen from Figure 13 that in terms of SOR activity, SS / NiNb₂O₆-NiSe₂ has a smaller E than SS / NiNb₂O₆ and SS / NiSe₂ 100 , and the E 100 vs. RHE values are respectively SS / NiNb₂O₆-NiSe₂ (0.286 V) < SS / NiSe₂ (0.398 V) < SS / NiNb₂O₆ (0.481 V). The above experimental results show that compared with the single-phase materials that have not been treated with metal oxysalt solution or selenized, the transition metal selenide-based heterojunction nanoarray electrode has more excellent activity in SOR.
[0140] Application Example 5 Performance Test of Electrocatalytic Sulfide Oxidation Reaction (SOR) The SOR activity test was carried out on Example 5 (CF / CoMoO₄-CoSe₂), Comparative Example 10 (CF / CoMoO₄) and Comparative Example 11 (CF / CoSe₂). The test method was the same as that in Application Example 1, and the results refer to Figure 14 .
[0141] As shown in Figure 14 , for the activity of SOR, compared with CF / CoMoO4 and CF / CoSe2, CF / CoMoO4-CoSe2 has a smaller E 100 , and the E 100 vs. RHE values are respectively CF / CoMoO4-CoSe2 (0.294 V) < CF / CoSe2 (0.391 V) < CF / CoMoO4 (0.529 V). The above experimental results show that, compared with single-phase materials that have not been treated with metal oxysalt solution or selenized, the transition metal selenide-based heterojunction nanoarray electrode has more excellent activity in SOR.
[0142] Application Example 6 Performance Test of Electrocatalytic Sulfide Oxidation Reaction (SOR) SOR activity tests were carried out on Example 6 (TM / FeWO4-FeSe2), Comparative Example 12 (TM / FeWO4) and Comparative Example 13 (TM / FeSe2). The test method is the same as that in Application Example 1, and the results refer to Figure 15 .
[0143] As shown in Figure 15 , for the activity of SOR, compared with TM / FeWO4 and TM / FeSe2, TM / FeWO4-FeSe2 has a smaller E 100 , and the E 100 vs. RHE values are respectively TM / FeWO4-FeSe2 (0.349 V) < TM / FeSe2 (0.428 V) < TM / FeWO4 (0.475 V). The above experimental results show that, compared with single-phase materials that have not been treated with metal oxysalt solution or selenized, the transition metal selenide-based heterojunction nanoarray electrode has more excellent activity in SOR.
[0144] In summary, the transition metal-based heterojunction nanoarray electrode material provided by the present invention is prepared through three steps: first, the current collector is placed in a mixed solution of transition metal salt and organic ligand for reaction to obtain a metal-organic ligand precursor array material; then the precursor array material is placed in a solution containing metal oxysalt for treatment; finally, it is prepared through a high-temperature gas-solid reaction with a selenium / tellurium source. The above material can be used as an electrocatalytic material, exhibiting excellent catalytic activity and stability in the sulfide oxidation reaction (SOR), and providing an efficient and green solution for sulfur-containing wastewater treatment.
[0145] The above examples are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above examples. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement manners and shall all be included within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal-based heterojunction nanor array electrode material, characterized in that, Includes the following steps: S1: The current collector is placed in a mixed solution containing transition metal salts and organic ligands, and after full reaction and post-processing, metal-organic ligand precursor array material is obtained; S2: The metal-organic ligand precursor array material obtained in step S1 is placed in a solution containing metal oxophosphates for treatment, and after full reaction and post-treatment, metal-organic ligand materials modified with metal oxophosphates are obtained. S3: Under a protective gas atmosphere, the metal-organic ligand material modified with metal oxophosphate obtained in step S2 and the heat conversion source are subjected to a high-temperature gas-solid reaction at 200~700 °C to obtain a transition metal-based heterojunction nanoarray electrode material. The heat conversion source includes a selenium source and / or a tellurium source; The metal in the metal oxometalate is selected from at least one of Sn, V, Mo, W, Ge, and Nb.
2. The method as described in claim 1, characterized in that, The metal in the transition metal salt is selected from at least one of Ti, Mn, Fe, Ni, Cu, Zn, Co, Mo, W, La, Ce, and Eu.
3. The method as described in claim 1, characterized in that, The organic ligand is selected from at least one of imidazole compounds, aromatic carboxylic acid compounds, and aliphatic polyol compounds.
4. The method as described in claim 1, characterized in that, The selenium source includes selenium powder.
5. The method as described in claim 1, characterized in that, The tellurium source includes tellurium powder.
6. The method as described in claim 1, characterized in that, The mass ratio of the metal-organic ligand material modified with the metal oxoate to the thermal conversion source is 1:(0.5~30).
7. The method as described in claim 1, characterized in that, The molar ratio of the transition metal salt to the organic ligand is 1:(0.2~20).
8. The transition metal-based heterojunction nanoarray electrode material prepared by the preparation method according to claims 1 to 7.
9. The application of the transition metal-based heterojunction nanoarray electrode material according to claim 8 in sulfide oxidation reactions.
